The Real and Nature: A Heretical Nature contra Philosophy’s Nature - Smith, Anthony Paul (Identities: Journal for Politics, Gender and Culture, 2011)
Author(s): Anthony Paul Smith Title (English): The Real and Nature: A Heretical Nature contra Philosophy’s Nature Journal Reference: Identities: Journal for Politics, Gender and Culture, Vol. 8, No. 2 (Summer 2011) Publisher: Department of Gender Studies, Euro-Balkan Institute Page Range: 55-67 Page Count: 12 Citation (English): Anthony Paul Smith, “The Real and Nature: A Heretical Nature contra Philosophy’s Nature,” Identities: Journal for Politics, Gender and Culture, Vol. 8, No. 2 (Summer 2011): 55-67.